Frequency of detection of allergic reactions to food in children with atopic dermatitis and pathology of the gastrointestinal tract - T.O. Kryuchko; L.M. Bubyr; I.M. Nesina; O.Ya. Tkachenko (Zaslavsky O.Yu., 2019)
Background. In recent years, there has been a worldwide tendency to steady increase in the incidence of adverse reactions caused by food. Therefore, at the present stage, the investigation of the prevalence of the main causative factors of the development of food hypersensitivity is still a challenging task for researchers. The purpose was to study the range of food products, which are the most likely allergy-causing for children of the Poltava region, who had a history of unwanted allergic reactions to food. Materials and methods. The study involved 242 children aged from 6 to 15 years, who had a history about adverse reactions caused by food. The basic group included 128 patients with inflammatory diseases of the upper gastrointestinal tract; the comparison group involved 114 children with atopic dermatitis. The detection of the frequency of allergic reactions to food was investigated by using a questionnaire, allergic anamnesis and findings obtained by skin prick tests with food, epidermal, household and pollen allergens. Results. The study has demonstrated that the factors significantly increasing risks of skin and gastrointestinal allergies in the examined children are as following: maternal hereditary burden of allergic diseases; non-compliance in pregnancy, when mothers of examined children neglected to stick to the hypoallergenic diet; early mixed and bottle feeding and improper introducing of solid food. The findings obtained by questionnaire and skin allergic tests demonstrated a higher level of food sensitization in the children of the basic group. It has been also found out that the development of adverse reactions, regardless of skin or gastrointestinal manifestations, is the most often observed when taking cow's milk, eggs and fish. Conclusions. Thus, the conducted studies have contributed in finding out main risk factors for the development of food hypersensitivity in children and in identifying the most etiologically significant food products that can provoke the development of allergic and gastroenterological diseases.